Achieving a full color palette with thickness, temperature, and humidity in cholesteric hydroxypropyl cellulose - Ren, Hongning; Balcerowski, Tadeusz; Dumanli, Ahu Gümrah (Frontiers in Photonics, 2023)
Hydroxypropyl cellulose (HPC) is a sustainable, cost-efficient, and bio-compatible cellulose derivative that forms cholesteric liquid crystalline phases in highly concentrated water solutions. While there have been studies exploiting HPC’s structural coloration and transferring the cholesteric order of the solutions into solid form via cross-linking and heat treatments, there is still a lack of understanding of the mechanisms that enable the transfer of the structural ordering of the HPC at high temperatures. In this work, we demonstrate the balance between temperature, humidity, and film thickness to achieve a full-color palette of pure HPC. While the cholesteric phase is trapped by water evaporation, the formation of a dense skin on the gels enables a thermal expansion of the encapsulated HPC gel during the heat treatment. Increasing the thickness, applying higher curing temperatures, and exposing the samples to higher humidity during the evaporation all result with increased pitch values that cause a red-shift in coloration in the solid state. Our analysis of the HPC samples cured in controlled temperature and humidity conditions at a fixed thickness provided an understanding of the dominance of the thermal expansion which drives the final structural organization in the solid cholesteric phase. When the thickness of the films was varied against fixed temperature and humidity conditions, the color shift from red to violet follows the thickness gradient of the sample due to the change in the curing time required to reach the solid form